SEJARAH PERADILAN MASA DINASTI ABBASIYAH: KEBIJAKAN SISTEM PERADILAN OLEH KHALIFAH HARUN AR-RASYID - Syarifa, Maharani; Aufa, Mumtaz Zuhda; Advani, Rayhan Ramadhan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2023)
The Abbasid dynasty was in control of Islamic government after the Umayyad dynasty, during whose reign the Abbasid dynasty was known in history as the golden age. It is called Abbasid because this dynasty was founded by the descendants of al-Abbas who was the uncle of the Prophet Muhammad Saw. In this period which is known as the golden age, there is a history of the world of Islamic justice which has had many developments regarding the justice system in it. In this writing, the history of Islamic justice during the Abbasid dynasty will focus on the reign of the caliph Harun ar-Rashid. Caliph Harun ar-Rasyid himself held caliphate power in the Abbasid dynasty from 170 AH - 193 AH or for 23 years. During his reign, Caliph Harun ar-Rashid appointed Abu Yusuf Ya'qub bin Ibrahim as qadhi al-qudha'. This research was conducted to find out what the Abbasid dynasty's justice system was like as well as the government and justice system during the time of Caliph Harun ar-Rasyid. The research method used in this research is descriptive qualitative, namely through literature studies from various literature.